Neuropsychiatric Manifestations and Neuroimaging Changes of Neurologic Wilson Disease–A Cross Sectional Study - Kundu, Gopen Kumar; Mukib, ABM (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Wilson disease is genetic disorder of copper metabolism which causes hepatic & neurologic manifestation mainly. Chelator therapy is usually given as first line treatment in symptomatic wilson disease. Objective: Objective of our study was to evaluate the neuropsychiatric menufestations of wilson disease. Methods: A Cross sectional study was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, a tertiary care premier Postgraduate Medical Institution of Bangladesh. Forty five (45) patients of neurologic wilson disease were evaluated at In-patient department of Paediatric Neurology, during the period of January 2015 to December 2020. Diagnosis of Neurologic wilson disease was done, based on the characteristic clinical features of progressive deterioration of scholastic performances, dysarthria and gait disorder along with ophthalmologic findings, biochemical & neuroimaging findings. Results: Total numbers of studied cases were 45. Mean age was 124.65± 20.69 months and male to female ratio was 1.8:1. Most of the patient (83.33%) arrived from poor socio-economic background and rural area (66.67%) of Bangladesh. Among them 20.0% had history of consanguineous mating parents and 17.78% had another affected sibs. Common presenting features were progressive deterioration of school performance (89.74%), gait disturbance (92.31%), dysarthria (92.31%) and dystonia (41.03%) of our studied children. Neuropsychiatric manifestations were very common among the affected children. Changes in behavior was present in 62.22% cases, and among them mania were present in 57.77% children. Other common neuropsychiatric manifestations were depression (35.55%), generalized anxiety disorder in 31.11% and loss of memory in 20% cases. Ophthalmological manifestations like KF ring (83.33%) also found in majority of patient. Neuroimaging study showed basal ganglia hyperintensity in 63.63.% , white matter hyper intense signal changes 18.18% cases and ischemic change in grey matter in 18.18% cases. Conclusion: In our study about two third cases of Neurologic Wilson diseases may present with Neuropsychiatric manifestations in children. Behavior changes were commonest neuropsychiatric manifestations which includes depression, mania, generalized anxiety disorder and loss of memory.In neuroimaging study bilateral basal ganglia hyperintensity were found in about three-fourth cases of our studied children. J Bangladesh Coll Phys Surg 2024; 42: 144-148